Effect of Decentralization on Health Service Delivery in Lower Local Government: A Case Study of Kasodo Health Center III Kasodo Sub County Pallisa District - Duchu Patrick (Uganda Christian University, 2024)
Ferlic & Steane, (2022) found out that in earlier centuries when little was known about the causes of diseases, societies tended to attribute illnesses to witch craft and resignation, and on this note, few public health actions were taken. As understanding of sources of contagion and means of controlling diseases became more refined, more effective health interventions against health threats were developed and the move towards decentralization started evolving especially with the emergence of the New Public Management (Manning, 2021) and Public organizations and agencies were formed to employ newly discovered interventions against health threats. It is important to note that the transformation of the territorial structure of Government, its decentralization, particularly the introduction of territorial self-Government was considered an essential task in the process of rebuilding political and administrative systems in Central and Eastern Europe after 1989 and the reforms of the territorial Government followed closely after the collapse of the Communist regimes and after the transformations of the constitutional bodies and Central Governments in 1990 (Batley & Larbi, 2014). This was intensified with intensions of extending power, public services, and generally public administration near to the locals through a scientific approach, through this approach, public authorities expanded to take on new tasks, including sanitation, immunization, regulation, health education, and personal health care (Chave, 1984; Fee, 1987). Since the 1980s, a great number of Countries, developed or developing, have been embarking on improving the quality of public service delivery through decentralization whereby legally Uganda embraced the move in 1997 through the enactment of the Local Government Act, 1997 (The Government of Uganda, 1997).